Arts, Religion, and the Environment: Exploring Nature's Texture - Bergmann, Sigurd (Studies in Environmental Humanities Ser, 2018)
Intro -- Arts, Religion, and the Environment: Exploring Nature's Texture -- Copyright -- Contents -- Notes on Contributors -- 1 Introduction: Exploring Nature's Texture -- Part 1: Seeing -- 2 With-In: Towards an Aesth/Ethics of Prepositions -- 3 The Atmospheric Turn -- Part 2: Wondering -- 4 Wonder and Ernst Haeckel's Aesthetics of Nature -- 5 Art without an Object but with Impact -- 6 Between Science and Art: An Anthropological Odyssey -- Part 3: Connecting -- 7 The Black Wood: Relations, Empathy and a Feeling of Oneness in Caledonian Pine Forests -- 8 Cultivated and Governed or Free and Wild? On Assessing Gardens and Parks Aesthetically -- 9 Where Embodiment Meets Environment: A Meditation on the Work of Hans Breder and Ana Mendieta with an Accompanying Interview with Hans Breder -- 10 Conclusion: The Aesthetic Roots of Environmental Amnesia: The Work of Art and the Imagination of Place -- Index